2023
DOI: 10.7554/elife.80950
|View full text |Cite
|
Sign up to set email alerts
|

GluA3 subunits are required for appropriate assembly of AMPAR GluA2 and GluA4 subunits on cochlear afferent synapses and for presynaptic ribbon modiolar–pillar morphology

Abstract: Cochlear sound encoding depends on α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs), but reliance on specific pore-forming subunits is unknown. With 5-week-old male C57BL/6J Gria3 knockout mice (i.e., subunit GluA3KO) we determined cochlear function, synapse ultrastructure and AMPAR molecular anatomy at ribbon synapses between inner hair cells (IHCs) and spiral ganglion neurons. GluA3KO and wild-type (GluA3WT) mice reared in ambient sound pressure level (SPL) of 55-75 dB had similar aud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 102 publications
0
30
1
Order By: Relevance
“…Next, we compared the PSD surface area and volume between modiolar side and pillar side and did not observe any difference in GluA3 WT (surface area p = 0.52; volume p = 0.10, unpaired t-test) (Figs. 7 and 8A top; Table 1). In contrast, male GluA3 WT PSDs were larger on the modiolar side (Rutherford et al, 2023). Data from single ultrathin sections showed that the PSD linear length was similar between the modiolarand pillar-side synapses (p = 0.93, Mann-Whitney test) (Fig.…”
Section: Pre-and Post-synaptic Ultrastructural Features Of Ihc-ribbon...mentioning
confidence: 83%
See 1 more Smart Citation
“…Next, we compared the PSD surface area and volume between modiolar side and pillar side and did not observe any difference in GluA3 WT (surface area p = 0.52; volume p = 0.10, unpaired t-test) (Figs. 7 and 8A top; Table 1). In contrast, male GluA3 WT PSDs were larger on the modiolar side (Rutherford et al, 2023). Data from single ultrathin sections showed that the PSD linear length was similar between the modiolarand pillar-side synapses (p = 0.93, Mann-Whitney test) (Fig.…”
Section: Pre-and Post-synaptic Ultrastructural Features Of Ihc-ribbon...mentioning
confidence: 83%
“…Thus, GluA4-only synapses were seen only in GluA3 KO for females in ambient or quiet conditions. Although GluA4-only synapses were significantly greater in number in GluA3 KO males than WT raised in ambient conditions (Rutherford et al, 2023), the differences did not reach statistical significance for the females (All synapses ambient, Fig. 3E Next, we compared synapse size and protein expression based on immunofluorescence volume and intensity per synapse, displayed as means per image and per group after normalizing metrics from individual images to the respective WT mean for images from ambient or quiet conditions (Fig.…”
Section: Ambient Sound Triggers Synaptopathy In Female Glua3 Ko Micementioning
confidence: 99%
“…The amplitude and latency of ABR wave I have been reported to reflect the function of cochlear ribbon synapses. ,, Thus, we further examined the changes in the ABR wave I amplitude and latency in this study. The NE group exhibited significantly decreased amplitudes of ABR wave I at all tested frequencies compared to the control group.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, efforts are required also to elucidate the molecular and structural knowledge regarding the PSD of the postsynaptic SGNs. Immuno‐electron microscopy and confocal and superresolution immunofluorescence have established the notion that a ~ 0.5–1.5 μm sized dense array of glutamate receptors with a ring‐like structure likely surrounding the presynaptic AZ (Matsubara et al , 1996; Meyer et al , 2009; Wong et al , 2014; Rutherford et al , 2023) ensures efficient detection of glutamate. A number of postsynaptic density proteins such as PSD‐95, Shank, and Homer1 have been identified (e.g., Davies et al , 2001; Reijntjes et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, opposing size gradients (decreasing in pillar–modiolar direction for AMPA receptor clusters, but in modiolar–pillar direction for ribbon size) have been described for IHCs of CBA mice (Liberman et al , 2011; Reijntjes et al , 2020), but while the presynaptic gradient was consistently found in two other mouse lines, the postsynaptic gradient was not (Reijntjes et al , 2020). A recent detailed study of the PSD of the IHC‐SGN synapse in C57BL/6J mice revealed a modiolar–pillar gradient of PSD size and showed that the GluA3 is required for modiolar–pillar gradient of ribbon size (Rutherford et al , 2023).…”
Section: Introductionmentioning
confidence: 99%